Challenges in a population-based registry of cardiovascular disease in Shiga, Japan. (13th November 2019) - Fujii, T; Arima, H; Yamamoto, T; Sawayama, Y; Takashima, N; Kita, Y; Tanaka, S; Miyamatsu, N; Miura, K; Nozaki, K
Abstract: Background: Stroke and cardiovascular disease are one of the leading causes of death and disability in Japan. In order to investigate current burden, we conduct a population-based registry of cardiovascular disease in Shiga Prefecture, Japan since 2012. We will demonstrate challenges in conduct of the registry study. Methods: In 2012, we established the Shiga Stroke Registry (SSR), a multicenter population-based registry study designed to build a complete information system for the management of stroke in Shiga Prefecture, Japan. The registry uses local monitoring, combined with remote data collection and quality control systems, to create an integrated surveillance system among a network of all acute care hospitals with neurology/neurosurgery facilities and smaller hospitals with rehabilitation facilities in the region. In 2019, study name has changed to Shiga Stroke and Heart Attack Registry (SSHR) and additional registration of coronary heart disease and aortic disease have started. Each case is reviewed and adjudicated by 2 or more specialists. Results: In the financial year of 2018 (from April to March), a total of 4809 stroke cases were identified. From December 2018 to April 2019, a total of 515 coronary heart and aortic diseases were identified. A total 10 nurses work full-time for the registry and it takes average of 1 hour to collect information for each patient. Challenges in conduct of the cardiovascular registry involve regulatory and ethical approval, funding, associations with local hospitals, non-standardized hospital diagnosis, staff training for comprehensive data collection including pathophysiology, examination and treatment, and quality control of data collection. Conclusions: SSHR is a population-based registry of wide range of stroke and cardiovascular disease in Shiga Prefecture, Japan. In order to keep quality of the data, we put a lot of efforts on staff training and quality control. Key messages: Population-based registry of wide range of stroke and cardiovascular disease in Shiga, Japan. In order to keep quality of the data, we put a lot of efforts on staff training and quality control.